The bell tower of the Kievo-Pechers'ka Lavra Monastery, Ukraine. - Jeremy Younkin:::Creator::::::::::::
A photo of the bell tower of the Kievo-Pechers'ka Lavra Monastery (Monastery of Caves), in the Dnipro Hills. The 316 ft. (96,5m) tall tower was built between 1731 & 1744. This monastery was founded in 1051 in the Dnipro caves, and became the spiritual center of the country ('Lavra' is a title given to important churches) and of Russians (Russians were introduced to Christianity in this country). The buildings of the monastery, which take up 30 hectares, were made in the 1600s & 1700s in the Ukrainian Baroque style. This wall has since been repaired. This photo mimics that taken by Capa. Color.